Precipitation behavior and tensile properties of A356.2 alloy with different high temperature pre-precipitation temperatures. (8th February 2022) - Ding, Yuming; Chang, Liang; Guo, Binxu; Ding, Jian; Chen, Xueguang; Tang, Ying; Song, Kaihong; Xia, Xingchuan
Abstract: In order to understand the effect of high temperature pre-precipitation (HTPP) temperature on the precipitation behavior and tensile properties of A356.2 alloy treated by Al-6Sr-7La master alloy, SEM, TEM and tensile tests were applied to investigate the evolution of fracture morphology and precipitates of the alloys under different HTPP temperatures. The results showed that ultimate tensile strength (UTS) and yield strength (YS) of the alloys decrease and elongation (El) increases with HTPP temperature decreasing. When HTPP temperature decreased from 510 °C to 470 °C coarsen coherent β ″ phase appear in α -Al matrix, continue to decrease HTPP temperature to 450 °C the main precipitate transformed into semi-coherent β ′ phase, leading to the change in mechanical properties. In addition, coarsening and transformation of the precipitate were attributed to the reduction of Si concentration which decreases with HTPP temperature decreasing. Moreover, Si nanoparticles precipitated in α -Al matrix, leading to the decrease of UTS and YS to certain extent due to reducing Si concentration during aging process.